Are first graders' arithmetic skills related to the quality of mathematics textbooks? A study on students' use of arithmetic principles. (February 2021) - Sievert, Henning; van den Ham, Ann-Katrin; Heinze, Aiso
Abstract: A major goal of the first years of schooling is students' development from using counting strategies to using calculation strategies – or even recall – to solve addition or subtraction problems. It requires the perception and usage of arithmetic principles. Although the continued use of counting strategies is problematic for further learning progress, they are frequently used by many students beyond Grade 1. While learning resources possibly play a role in students' development in this field, our knowledge about their impact is limited. In this study we investigated the presented learning opportunities of four different textbooks regarding arithmetic principles in Grade 1, and subsequently the relation to first graders' strategy use by analyzing a one-year dataset of 1614 students from 86 classes. The analyses show differences in the textbooks' quality concerning arithmetic principles as well as a considerable connection to students' strategy use at the end of Grade 1. Highlights: Grade 1 textbooks differ in their quality regarding arithmetic principles. Textbook quality is related to students' strategy use. Textbook quality explains a substantial amount of variance between classes.